2018
DOI: 10.1177/1934578x1801301211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biological Properties of Zederone and Zedoarondiol from Rhizomes of En-Lueang (Curcuma cf. amada)

Abstract: Curcuma cf. amada Roxb., also known as En-Lueang in Thailand, belongs to the Zingiberaceae family and grows from rhizomes. These rhizomes have been used in the Thai and Ayurveda systems of medicine. However, to our knowledge, no biologically active compounds isolated from En-Lueang have been reported. In this study, natural compounds were isolated from En-Lueang and their structures were determined by spectroscopic methods. The two isolated compounds were identified as zederone (1) and zedoarondiol (2) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Zederone and zedoarondiol, from rhizomes of En-Lueang (Curcuma cf. amada), show strong cytotoxicity in a leukaemic cell line and in peripheral blood mononuclear cells, as well as having antioxidant and haemolysis properties [41]. Dry extracts from rhizomes of C. xanthorrhiza and C. zedoaria have been shown to have anticancer and antiviral properties [42][43][44].…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
“…Zederone and zedoarondiol, from rhizomes of En-Lueang (Curcuma cf. amada), show strong cytotoxicity in a leukaemic cell line and in peripheral blood mononuclear cells, as well as having antioxidant and haemolysis properties [41]. Dry extracts from rhizomes of C. xanthorrhiza and C. zedoaria have been shown to have anticancer and antiviral properties [42][43][44].…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
“…In addition, Curcuma longa , a species of this genus, has been shown to have anti-inflammatory properties [ 22 ]. Potent cytotoxic activity in a leukemic cell line, hemolysis, and antioxidant activity have also been evaluated in Curcuma amada [ 23 ]. Moreover, in vitro analysis of volatile oils that are obtained from Curcuma caesia leaf has been shown to have extensive anti-inflammatory, antioxidant, and antibiotic effects [ 24 , 25 ].…”
Section: The Genus Curcumamentioning
confidence: 99%
“…10 C. amada has been tested for cytotoxic action in a leukemic cell line, hemolysis, and antioxidant activity. 11 In addition, in vitro testing of volatile oils extracted from C. caesia leaves revealed that they have potent anti-inflammatory, antioxidant, and antibiotic properties. 12,13 Bioactive components found in Curcuma species include flavonoids, monoterpenes, sesquiterpenes, phenolic compounds, and antioxidants.…”
Section: Introductionmentioning
confidence: 99%